Impacts des changements climatiques sur les arboviroses dans une île tropicale en développement (Mayotte) - Jauze Laurent; Arnoux Stéphane; Bagny Leïla (VertigO, 2010)
Mayotte is a small island in the South West Indian Ocean where the tropical climate is particularly favorable to vector-borne diseases. The presence of various mosquito, vectors of arboviruses is a significant health risk for the population. This article attempts to assess the the consequences of a changing thermal regime on populations of Aedes mosquitoes, by studying the life traits of species and conducted in a controlled environment. It seems that the rise of the temperature planned for the year 2100 would be too small to have an effect on the incidence of some diseases carried by mosquitoes. In fact, more than the climatic variables, this is more the human context that would be the most influential epidemiological risk in Mayotte. The hypothesis is expressed that this is not climate change that would increase health risks but that the change in political status that would limit them.